Presepsin as a diagnostic biomarker for sepsis across neonates, children, and adults: A meta-analysis - Kaicheng Peng; Xiangmin Zhang; Qinyuan Li; Zhengxiu Luo (Biomolecules & Biomedicine)
Sepsis remains a leading global health challenge, with delayed recognition and limited diagnostic accuracy of current tools contributing to high morbidity and mortality. Conventional clinical scores (SOFA/qSOFA), standard biomarkers (CRP, PCT), and blood cultures suffer from delayed responsiveness, insufficient specificity, or slow turnaround, underscoring the urgent need for more reliable early diagnostic strategies. Presepsin, a soluble CD14 subtype generated during pathogen recognition by innate immune cells, has emerged as a promising biomarker with potential to reflect infection status earlier and more specifically than traditional markers. This systematic review and meta-analysis quantitatively evaluated the diagnostic accuracy of presepsin across diverse populations. PubMed, EMBASE, Web of Science, and Cochrane Library were searched for studies published between 2015 and 2025. Forty-seven studies involving 7,087 participants were included. Pooled sensitivity, specificity, diagnostic odds ratio (DOR), area under the curve (AUC), and likelihood ratios (PLR/NLR) with 95% confidence intervals (CI) were calculated using random-effects models. Heterogeneity was assessed with I² statistics, meta-regression, and subgroup analyses. Study quality was evaluated using QUADAS-2. Presepsin demonstrated excellent overall diagnostic performance: pooled sensitivity 0.84 (95% CI: 0.81–0.88), specificity 0.86 (95% CI: 0.80–0.90), DOR 32.23 (95% CI: 20.11–51.66), and AUC 0.91 (95% CI: 0.88–0.93). Subgroup analyses confirmed robust performance across settings and populations, with particularly high accuracy in neonates (sensitivity 0.90, specificity 0.92, AUC 0.96), followed by children (sensitivity 0.84, specificity 0.81, AUC 0.88, NLR 0.20) and adults (sensitivity 0.81, specificity 0.82, AUC 0.87). Meta-regression identified year of publication, geographic region, specimen type, population, and diagnostic criteria as key contributors to heterogeneity, but sensitivity analyses confirmed result stability. No significant publication bias was observed (p = 0.33). In conclusion, presepsin is a valuable and highly promising biomarker for sepsis diagnosis, showing favorable diagnostic accuracy across populations, with strongest utility in neonates. Its application in pediatric and adult patients warrants further validation through large, prospective, multi-center studies.